The local rotation curve of the Milky Way based on SEGUE and RAVE data - Sysoliatina, Kseniia; Just, Andreas; Grebel, Eva K. (Astronomy and astrophysics, 2018)
Aims. We construct the rotation curve of the Milky Way in the extended solar neighbourhood using a sample of Sloan Extension for Galactic Understanding and Exploration (SEGUE) G-dwarfs. We investigate the rotation curve shape for the presence of any peculiarities just outside the solar radius as has been reported by some authors.Methods. Using the modified Strömberg relation and the most recent data from the RAdial Velocity Experiment (RAVE), we determine the solar peculiar velocity and the radial scale lengths for the three populations of different metallicities representing the Galactic thin disc. Subsequently, with the same binning in metallicity for the SEGUE G-dwarfs, we construct the rotation curve for a range of Galactocentric distances from 7 to 10 kpc. We approach this problem in a framework of classical Jeans analysis and derive the circular velocity by correcting the mean tangential velocity for the asymmetric drift in each distance bin. With SEGUE data we also calculate the radial scale length of the thick disc taking as known the derived peculiar motion of the Sun and the slope of the rotation curve.Results. The tangential component of the solar peculiar velocity is found to be V ⊙ = 4.47 ± 0.8 km s−1 and the corresponding scale lengths from the RAVE data are Rd(0 < [Fe/H] < 0.2) = 2.07 ± 0.2 kpc, Rd(−0.2 < [Fe/H] < 0) = 2.28 ± 0.26 kpc and Rd(−0.5 < [Fe/H] <−0.2) = 3.05 ± 0.43 kpc. In terms of the asymmetric drift, the thin disc SEGUE stars are demonstrated to have dynamics similar to the thin disc RAVE stars, therefore the scale lengths calculated from the SEGUE sample have close values: Rd(0 < [Fe/H] < 0.2) = 1.91 ± 0.23 kpc, Rd(−0.2 < [Fe/H] < 0) = 2.51 ± 0.25 kpc and Rd(−0.5 < [Fe/H] <−0.2) = 3.55 ± 0.42 kpc. The rotation curve constructed through SEGUE G-dwarfs appears to be smooth in the selected radial range 7 kpc < R < 10 kpc. The inferred power law index of the rotation curve is 0.033 ± 0.034, which corresponds to a local slope of dV c∕dR = 0.98 ± 1 km s−1 kpc−1. The radial scale length of the thick disc is 2.05 kpc with no essential dependence on metallicity.Conclusions. The local kinematics of the thin disc rotation as determined in the framework of our new careful analysis does not favour the presence of a massive overdensity ring just outside the solar radius. We also find values for solar peculiar motion, radial scale lengths of thick disc, and three thin disc populations of different metallicities as a side result of this work.